Análise epistemológica das pesquisas em contabilidade publicadas em periódicos nacionais - Gomes, Gilvania de Sousa (2013)
This study aimed to perform an epistemological analysis of Brazilian publications in national journals recognized by CAPES occurred in the years 2007 to 2011, based on a sample of 198 articles from eleven journals. For this, we used the space initially proposed by methodological quadripolar Bruyne, and Schoutheete Herman (1991), applied to studies in the area of Administration by Martins (1994) then used by Theóphilo (2000), Theóphilo (2004) and Botelho ( 2012) in accounting. Such analysis methodology covers the Poles Epistemological, Theoretical, Methodological and Technical. Content analyzes were performed in order to compose a database with information about the texts read. Among the highlights are the results of research to the prevalence of Theoretical and empirical type (51%); issues addressed more focus on thematic areas of Accounting for External Users (36%), Management Accounting and Controlling (19%) and Education and Accounting Research (19%). Pole Epistemological it appears that the Break occurs between the object and the object of scientific common sense in 73% of the research, the problem is clearly stated in 69% of the work and principles of preparation of the scientific object was observed on average by 89% cases. The Pole Theory emphasizes that 94% of the sample shows the theoretical stance Positive great Positivist theory is in 83% of texts and approaches to theories are mostly Macroeconomic. Regarding methodological aspects, the positivist approach was detected in 75% of articles. Of research strategies, the almost experiment was the predominant (30%), data on 43% of surveys were collected in a Documentary. The Descriptive Statistics toolset contains the most recurrent in the studies analyzed (39% of all uses). The total work 108 (55%) emphasizes on contemporary events. Most analyzed articles (141) further specifies the steps of its construction, to allow replication and other possible scenario. Future studies may make comparisons between aspects of Brazilian research with international and pointing their similarities and differences, see if there are relations between the profile of research published in journals and training for members of its editorial board and perform statistical analyzes to assess the degree of relationship Among the features of the studies.